1985
DOI: 10.7164/antibiotics.38.242
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of chrysomycins A and B origin of the chromophore.

Abstract: The biosynthetic origin of the carbon atoms in the chromophores of chrysomycins A and B was investigated in feeding experiments using 13C labeled acetates and propionate.A biosynthetic scheme is proposed involving the condensation and rearrangement of a decaketide intermediate which contains either propionate (chrysomycin A) or acetate (chrysomycin B) as the chain initiator.The isolation of chrysomycin was first reported in 1955 by STRELITZ and coworkers1) who were screening for antibiotics with activity again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
61
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 13 publications
2
61
0
Order By: Relevance
“…Also the very !nteresting antitumor antibiotics of the gilvocarcin class [226][227][228][229][230][231][232][233][234][235][236][237][238][239][240][241] The key biosynthetic step is an oxidative cleavage of the 6a,7-bond of an angucyclinone, presumably ochromycinone (35) ravidomycin (293), the chrysomycins A (294), and B (295), and thus BE-12406 A (296) and B (297, see Table 15), are all thought [226,229,230] to derive from a decaketide folded in the typical angucyclinone manner. Similarly as shown for the kinamycins and jadomycins, an oxidative C-C bond cleavage initiates excision of a single carbon, and further rearrangement leads to the typical lactone structures of the gilvocarcin class.…”
Section: Discussionmentioning
confidence: 99%
“…Also the very !nteresting antitumor antibiotics of the gilvocarcin class [226][227][228][229][230][231][232][233][234][235][236][237][238][239][240][241] The key biosynthetic step is an oxidative cleavage of the 6a,7-bond of an angucyclinone, presumably ochromycinone (35) ravidomycin (293), the chrysomycins A (294), and B (295), and thus BE-12406 A (296) and B (297, see Table 15), are all thought [226,229,230] to derive from a decaketide folded in the typical angucyclinone manner. Similarly as shown for the kinamycins and jadomycins, an oxidative C-C bond cleavage initiates excision of a single carbon, and further rearrangement leads to the typical lactone structures of the gilvocarcin class.…”
Section: Discussionmentioning
confidence: 99%
“…Incorporation experiments showed that the gilvocarcin, ravidomycin, and chrysomycin backbone derived from acetate and propionate, and it was suggested that the pathway involves an oxidative rearrangement of an angucyclinone intermediate. [3133] We recently isolated the GV gene cluster and characterized various genes through inactivation and cross complementation experiments. [14,3437] However, our efforts to address the biosynthetic sequence of key post-PKS tailoring events and their relevant intermediates were hampered by the resistant nature of the producer strain for genetic manipulations, and the inability of several mutant constructs to express in a heterologous host.…”
Section: Introductionmentioning
confidence: 99%
“…NGC 7469 is also a noted example of variability amongst Seyfert galaxies. UBV or UBVR photometry has been undertaken in the Crimea since 1967 (Doroshenko, Lyutyi & Rakhimov 1989, 1990Chuvaev, Lyutyi & Doroshenko 1990). Shorter series of observations have been made by Penston et al (1974) and Penfold (1979).…”
Section: Introductionmentioning
confidence: 99%